2021
DOI: 10.1519/jpt.0000000000000316
|View full text |Cite
|
Sign up to set email alerts
|

Circumstances and Factors Associated With Falls Among Community-Dwelling Older Adults Diagnosed With Heart Disease Using the International Mobility in Aging Study (IMIAS)

Abstract: Simple and multiple logistic regressions identified which clinical factors were associated with falling. Results: A total of 429 older adults with CVD (mean age 69.5 ± 2.9) and 431 older adults without CVD (69.2 ± 2.9) participated in the study. Approximately 53% of fallers with CVD had 2 or more falls compared with fallers without CVD (39%). The most common location for falling was at home (43%) for fallers with CVD or in the street (50%) for fallers without CVD. Approximately 9% of fallers with CVD needed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Physical labor may negatively affect the muscle strength and endurance of older women and further weaken their balance ability and mobility (33). Older people with heart disease are prone to a series of symptoms, such as dyspnea and chest pain, which may indirectly lead to falls (34). Aburub et al (34) showed that older adults with cardiovascular diseases have a greater risk of falls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical labor may negatively affect the muscle strength and endurance of older women and further weaken their balance ability and mobility (33). Older people with heart disease are prone to a series of symptoms, such as dyspnea and chest pain, which may indirectly lead to falls (34). Aburub et al (34) showed that older adults with cardiovascular diseases have a greater risk of falls.…”
Section: Discussionmentioning
confidence: 99%
“…Older people with heart disease are prone to a series of symptoms, such as dyspnea and chest pain, which may indirectly lead to falls (34). Aburub et al (34) showed that older adults with cardiovascular diseases have a greater risk of falls. Many studies have confirmed that when older adults sleep less than 6 h, the occurrence and frequency of falls increase significantly (35,36).…”
Section: Discussionmentioning
confidence: 99%